(untitled) - Healey, Marcus J (New York, NY, 1998)
The implementation of pollution prevention requires diverse engineering and management practices that reduce or preclude the pollution that reaches the air, water or soil. This handbook provides business and technical managers with straightforward guidance on how to perform pollution prevention. The accompanying software is industry- and process-tailored to assist managers in developing plans specific to their businesses. Concentrating on the technical and practical, this handbook and software provide practitioners with the tools to develop pollution prevention plans and to enable their businesses to receive the economies and benefits of implementation. (Publisher description)
Keywords: Industrial management,Pollution; Environmental aspects.,Economic aspects